Brands as relationship partners: Warmth, competence, and in‐between - Fournier, Susan; Alvarez, Claudio (Journal of Consumer Psychology, 2012)
AbstractThe dialogue between social perception and consumer–brand relationship theories opens new opportunities for studying brands. To advance branding research in the spirit of interdisciplinary inquiry, we propose to (1) investigate the process of anthropomorphism through which brands are imbued with intentional agency; (2) integrate the role of consumers not only as perceivers but also as relationship agents; (3) consider important defining dimensions of consumer–brand relationships beyond warmth and competence, including power and excitement; and (4) articulate the dynamics governing warmth (intentions) and competency (ability) judgments to yield prescriptive guidance for developing popular and admired brands.